Korelasi antara Dukungan Orang Tua dengan Motivasi Belajar Anak Selama Menerima Pembelajaran Daring di SD Kota Bengkulu - Afifah Qumariah; Feri Noperman; Dalifa M.Pd. (Universitas Bengkulu, 2022)
This study aims to determine the correlation between parental support and children's learning motivation while receiving online learning during covid-19 in Bengkulu City. This study uses a quantitative approach to the type of correlation. The population of this study were students at SD Kota Bengkulu. The sample that the researchers used was 360 respondents. The research instrument used was a questionnaire. The steps in this study are data tabulation, validity test, reliability test, data description, normality test, hypothesis testing and conclusions. In this study concluded that: there is a positive and significant relationship between parental support learning motivation is based on the calculation of SPSS version 16 is equal to 0.501 and the results correlation rvaluecount is less than 0.05 then H0 is rejected and Ha accepted so that there is a correlation between parental support and student motivation. The correlation of 0.501 lies between 0.40-0.599, it can be concluded that there is a moderate correlation between parental support and student motivation while receiving online learning at SD Kota Bengkulu. Keywords: parental support, children's learning motivation.